Carbonated hydroxyapatite inflammation’s responses on local rabbits - Aryan Morita; Ngatidjan Ngatidjan; Setyo Purwono (Biomedical Engineering, 2014)
Objective: This study aimed to find out the response of mandible inflammation implanted with carbonated hydroxyapatite.  Methods: Sixty local rabbits were divided into three groups, including carbonatedhydroxyapatite (CHA) group; hydroxyapatite (HA) group; and control. Each group divided into 5 sub groups for observation in day-1, 3, 5, 7, and 14. On first day, all rabbits were anesthesized and incised to create cavity in the mandible. CHA or HA powder as much as 0,05 g were put into it. Then it was sutured using silk thread. Von Ebner method for decalcification were used followed by hematoxylin eosin staining to examine the neutrophil and macrophage. Results: The number of neutrophil, macrophage, and edema volumes in CHA group were lower than HA group. There were not any significant difference (p>0,05) between CHA, HA, and control.  Conclusion: There are no mandible inflammation response in CHA implantation and HA.Key Words: CHA; edema volumes; inflammation; macrophages; neutrophils